PENGALAMAN PERAWAT MENYAMPAIKAN BREAKING BAD NEWS DI SATU RUMAH SAKIT SWASTA DI BATAM [NURSES’ EXPERIENCES IN BREAKING BAD NEWS IN A PRIVATE HOSPITAL IN BATAM] - Onita, Onita; Natalia, Siska; Utami, Rizki Sari (Nursing Current: Jurnal Keperawatan, 2024)
In the field of palliative care nursing, Breaking Bad News (BBN) involves providing accurate information regarding the patient's status, which is often distressing for both the patient and their family. BBN is a collaborative endeavour including doctors and nurses. Patients frequently anticipate nurses to provide a reiteration of information previously conveyed by doctors. The phenomena are the lack of specialized training for nurses in Breaking Bad News (BBN), resulting in families frequently requesting nurses to provide further explanations on their health and treatment plan. The objective of this study was to investigate the firsthand encounter of nurses in BBN (Breaking Bad News). The approach employed qualitative phenomenology. 10 individuals were interviewed using semi-structured interviews to collect data. The Colaizzi Technique was employed for the analysis. Outcome: The study yielded four distinct themes: the collaborative efforts of nurses and doctors in BBN through therapeutic communication, the challenges faced by nurses when families lack understanding, the provision of BBN by nurses based on their professional experience, and the positive aspects observed by nurses in families. The study's findings revealed that nurses often face situations when they were required to Break Bad News (BBN), while lacking formal training in this domain. Nurses and doctors should undergo training in BBN (Breaking Bad News) to ensure they are sufficiently prepared to deliver such news to patients.BAHASA INDONESIA Dalam keperawatan paliatif, Breaking Bad News (BBN) memberikan informasi tentang kondisi pasien yang sebenarnya, yang sering kali merupakan berita buruk bagi pasien dan keluarganya. BBN merupakan peran kolaboratif antara dokter dan perawat. Fenomena yang terjadi adalah perawat tidak mendapatkan pelatihan khusus dalam menyampaikan BBN, dan perawat sering diminta oleh keluarga pasien untuk menjelaskan kembali informasi yang telah diberikan oleh dokter. Tujuan dari penelitian ini adalah untuk mengeksplorasi pengalaman perawat dalam memberikan BBN. Metode yang digunakan adalah fenomenologi kualitatif. Data dikumpulkan dengan wawancara semi-terstruktur dengan 10 partisipan. Analisis menggunakan Teknik Colaizzi. Hasil penelitian didapatkan empat tema, yaitu kolaborasi antara perawat dan dokter memberikan BBN dengan komunikasi terapeutik, perawat mengalami kesulitan saat keluarga tidak mengerti, perawat memberikan BBN berdasarkan pengalaman kerja, dan perawat melihat hal positif pada keluarga. Kesimpulan dari penelitian ini adalah perawat sering diminta untuk memberikan BBN, namun perawat belum pernah mendapatkan pelatihan khusus dalam memberikan BBN. Rekomendasi untuk perawat dan dokter agar mendapatkan pelatihan tentang BBN, sehingga perawat lebih siap dalam memberikan BBN kepada pasien.